HORMONALLY-INDUCED ABORTION AND PARTURITION IN GOATS AND EWES - Al-Saadi, H.K.; R. Abdul-Aziz, F.; H.Al-Attia, H. (The Iraqi Journal of Veterinary Medicine, 1989)
Induced abortion and parturition have been practiced in both goats and ewes following the hormonal treatments. The intervals between injection and parturition or abortion in goats were 47.29+ 3.981 and 47.5+2.872 hours with intramuscular injection of 1 ml. Luprostiol (each 1 ml. contains 7.5 mg. prostaglandin F2 x) and 58.8+6.681 and 91.2+6.652 hours with double intramuscular injection of 3 ml. corticotets (each 1 ml. contains 2.5 mg prednisolone acetate and 5 mg dexamethasone) respectively. The intervals between injection and either the parturition over 148 days or abortion at 138 days of gestation in ewes were 40.4+4.019 and 66.5+5.852 hours. respectively with double intramuscular injection of 3 ml. corticotets, however, there was no response with luprostiol. The commbination of the compounds gave better results in bothe the goat and ewes, although better results were obtained following Luprostiol treatment in goat and corticotets in ewes in both parturition and abortion.